Penguatan Literasi Digital Siswa SMK Muhammadiyah 2 Pontianak Melalui Program Pelatihan Pembuatan Website - istikoma isti; Suratno -; Rangga Aditya Saputra - (Ma'soem University, 2026)
This Community Service activity was carried out to address the lack of digital literacy of SMK Muhammadiyah 2 Pontianak students, particularly in the productive use of technology. The urgency of this activity is the existence of a gap between access to high technology but the ability of students to produce digital content is low. This research uses the Participative Action Research (PAR) method which consists of planning, implementing actions, evaluating and reflecting. This approach motivates students to be active in context-based and practice-based learning. Students not only learn but can be skilled immediately in creating and maintaining simple websites. Critical thinking, problem solving and collaborative practices of digital literacy of students. The main issues are the use of technology that is still consumptive and the limited learning practices in the curriculum (. As a result, they do not have the experience to build digital skills that can be applied and not ready to face the demands of technology-based world of work. So structured training is needed and according to industry needs. The results of the activity showed that students’ knowledge and skills in making websites increased by 45%. This activity also can increase the students’ positive attitude, creativity, and confidence in using the technology. This program has holistic, sustainable impacts in developing students’ digital literacy.